Hybrid energy design for lighter than air systems. (August 2021) - Gupta, Sowmya; Rajhans, Chinmay; Duttagupta, Siddhartha P.; Mitra, Mira
Abstract: Solar Powered Lighter Than Air (LTA) systems find applications in reconnaissance, surveillance, mapping of geographical locations, and environmental monitoring using electronic and communication sensor payloads. The system payload comprises an airborne LiDAR for cloud monitoring and a day-night vision camera for surveillance applications. The primary source of payload power is generated by lightweight and flexible solar photovoltaic modules integrated on the platform's top hull. The generated solar power is affected by wind velocity disturbances, dynamic cloud footprints, and inherent platform contour. The current objective is to design a hybrid energy scheme for uninterrupted payload operation in the presence of the aforementioned degrading factors. A zero-energy deficit design consisting of a diesel generator as an auxiliary power source has been proposed. The novelty of work lies in considering the combined effect of impact factors in the energy scheme for LTA system applications. Under the given environmental conditions, a power outage of 2.5 hours out of 11 operating hours was observed, which is satisfactorily compensated using the proposed hybrid design. The work presents detailed design of a practical and scalable hybrid system which ensures uninterrupted power under realistic environmental conditions.